Optimal reserve provision regulation for wind farms equipped with energy storage systems. (18th September 2018) - Yu, Moduo; Huang, Wentao; Tai, Nengling; Zheng, Xiaodong; Shi, Jinxiao
Summary: Uncertainty and fluctuation of wind energy threatens the stable and economical operation of power systems. Power systems need additional reserve to solve the problem. Wind farms have the potential of providing power reserve due to the flexible control ability of wind turbines (WT). This paper analyzes the potential and capability of wind farms providing active power reserve. Energy storage systems (ESS) are incorporated to improve the safety margin and to offset the influence of prediction errors. Based on the combination of ESS and WT, 3 optimal strategies are proposed on the basis of WT operating in a suboptimal status, which increases spinning reserve and economic effects. Study cases validate the increments of the spinning reserve and economic effects of the strategies. The results show that the proposed optimal dispatching strategies can be used practically in wind‐thermal power systems.